PENGEMBANGAN METODE PENANDA ISOZYME PADA TREMBESI - Titis Hutama Syah; Arbain Arbain (Jurnal Pemuliaan Tanaman Hutan, 2020)
Fifty samples of raintree from Sangatta, the capital city of Kutai Timur Regency, East Kalimantan were analyzed using isozyme markers to determine the characteristics of the banding pattern. The use of isozymes was intended as a biochemical marker for genetic diversity analysis. This study aimed to determine the enzyme system that could be used to determine genetic diversity of raintree. The enzyme systems used were diaphorase, esterase, and peroxidase. Polymorphism assessments were carried out on the parameters of expected heterozygosity (H), polymorphism information content (PIC), effective multiplex ratio (E), marker index (MI), discriminanting power (D), and Resolving (R). Among the three enzyme systems used, diaphorase showed consistent performance against each of the parameters assessed, with a value of H =0.475; PIC = 0.362; E =6.1; MI = 2,2; D = 0.63: and R = 4.44. However, esterase had the highest multiplex effective ratio (E = 6.16). Therefore, diaphorase is the best isozyme marker that can be used to analyze the genetic diversity of raintree.